A polyamide composition and its preparation method and application

By designing a halogen-free flame retardant system, an acidic group-containing vinyl copolymer and a composite coloring system in polyamide materials, the problem of color change in polyamide materials in high temperature environments is solved, and the material's excellent flame retardant and high temperature color stability are achieved.

CN117659689BActive Publication Date: 2025-02-28JIANGSU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311656428.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2025-02-28
Estimated Expiration
2043-12-05

AI Technical Summary

Technical Problem

Existing polyamide materials are prone to color changes in high temperature environments, resulting in reduced flame retardant performance and cannot meet the long-term high-temperature working environment needs of high-voltage connectors and other components.

Method used

通过设计和复配聚酰胺组合物中的无卤阻燃体系、含酸性基团的乙烯基共聚物和复合着色体系,提升材料的阻燃性和耐高温颜色稳定性。

Benefits of technology

It has achieved small color difference and good color stability after high-temperature baking, and can meet the performance requirements of high-voltage connectors, electronic appliances and new energy industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004589045070000031
    Figure BDA0004589045070000031
  • Figure BDA0004589045070000071
    Figure BDA0004589045070000071
Patent Text Reader

Abstract

The present invention provides a polyamide composition and a preparation method and application thereof, wherein the polyamide composition comprises the following components by mass: 20-60 parts of a polyamide resin, 13-30 parts of an organic phosphinate flame retardant, 4-10 parts of a synergistic flame retardant, 0.2-5 parts of a vinyl copolymer containing an acidic group, and 0.3-7 parts of a colorant. Through the design and mutual compounding of a halogen-free flame retardant system, a vinyl copolymer containing an acidic group, and a coloring system, the polyamide composition has excellent flame retardancy and high temperature resistance, small color difference after high-temperature baking, and good color stability, and can fully meet the performance requirements of high-voltage connectors, electronic appliances, and new energy industries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a polyamide composition and a preparation method and application thereof. Background Art

[0002] Polyamide (PA), commonly known as nylon, is an important thermoplastic engineering plastic. It is widely used in automobiles, mechanical parts, electronic appliances, home appliances, new energy and other fields due to its high strength, good self-lubrication, wear resistance, oil resistance and easy molding and processing. Since many application scenarios of polyamide have fire safety requirements, polyamide materials are also required to have excellent flame retardancy.

[0003] Organic phosphine flame retardant polyamide is a new material that has developed rapidly in recent years. Compared with traditional halogen flame retardant polyamide, organic phosphine flame retardant polyamide has obvious environmental advantages, and is easy to color, easy to process, excellent comprehensive mechanical properties, high tracking index (CTI) and other characteristics, and is widely used in high-voltage connectors and other parts. High-voltage connectors of new energy vehicles usually use RAL2003, RAL2004, RAL2009, RAL2010, RAL2011 and other colors as warning colors. Since high-voltage connectors are in a high-temperature working environment for a long time, the flame retardant polyamide in them is also often exposed to high temperatures. After long-term use, the color changes, resulting in the loss of the warning color effect. The acidity of organic phosphine flame retardant polyamide is stronger than other commonly used flame retardant polyamides, and it is easier to promote the degradation of nylon and certain color powders. Therefore, organic phosphine flame retardant polyamide is more likely to change color during long-term thermal oxidation aging.

[0004] CN102952391A discloses a flame retardant polyamide composition, comprising: 15-90 wt% aromatic polyamide; 5-30 wt% halogen-free flame retardant: specifically a mixture of one or more of hypophosphite, bisphosphite, hypophosphite polymer, and bisphosphite polymer; 0.1-10 wt% mica flakes; 15-40 wt% reinforcing agent; additives, including impact modifiers, ultraviolet light stabilizers, heat stabilizers, antioxidants, flow improvers, processing aids, lubricants, and colorants. The molded products made of the flame retardant polyamide composition can be used for electrical connectors, connector housings, interrupter housings, and relay housings, and have excellent flame retardancy, but the ultraviolet light stabilizers, heat stabilizers, antioxidants, etc. therein do not effectively solve the stability problem of the material, and there will still be obvious discoloration when exposed to high temperature for a long time.

[0005] CN110446756A discloses a thermoplastic molding composition, comprising the following components: 0-96.9 wt % of thermoplastic polyamide, 1-20 wt % of inorganic phosphinate, 1-15 wt % of organic phosphinate, 1-15 wt % of melamine cyanurate, 0.1 to 10 wt % of polyvinyl pyrrolidone, and 0-50 wt % of other additives; in the composition, the combination of inorganic phosphinate, organic phosphinate and melamine cyanurate improves flame retardancy and glow-wire test performance, and polyvinyl pyrrolidone helps to suppress the tendency of yellowing when heated and improves heat aging resistance, but its color difference when baked at 150°C for 24 hours is greater than 15, which still cannot meet the color stability requirements of flame-retardant polyamide under high temperature environment.

[0006] EP1950238A discloses a flame retardant polyamide composition with improved color stability, comprising the following components: 1) a semi-aromatic polyamide composition; 2) a flame retardant: at least one of phosphinate and its polymer, diphosphinate and its polymer; 3) a hindered phenol stabilizer; 4) a phosphite stabilizer; the composition does not contain a hindered amine stabilizer, or the content of the hindered amine stabilizer in all stabilizers is ≤15%. Although the combination of stabilizers in the composition improves the color stability, the color change is still obvious under high temperature conditions simulating the working environment of a high-voltage connector.

[0007] Therefore, developing a polyamide material having both excellent flame retardancy and high temperature resistant color stability is an urgent problem to be solved in the art. Summary of the invention

[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide a polyamide composition and a preparation method and application thereof. Through the design and compounding of the components, the polyamide composition has excellent flame retardancy and high temperature resistance, small color difference after high-temperature baking, good color stability, and can fully meet the performance requirements of high-voltage connectors, electronic appliances and new energy industries.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a polyamide composition, wherein the polyamide composition comprises the following components in parts by mass:

[0011]

[0012] The polymerizable monomers of the vinyl copolymer containing acidic groups include a combination of ethylene and unsaturated monomers containing acidic groups, and the mass percentage of the unsaturated monomers containing acidic groups in the polymerizable monomers is 1%-10%.

[0013] In the polyamide composition provided by the present invention, the organic phosphinate flame retardant is compounded with a synergistic flame retardant to construct a halogen-free flame retardant system with excellent flame retardancy; at the same time, the vinyl copolymer containing an acidic group can, on the one hand, have a coating effect on the halogen-free flame retardant system based on the acidic group therein, effectively inhibit the high-temperature decomposition of the flame retardant, and improve the baking color difference; on the other hand, the vinyl copolymer containing an acidic group has a toughening effect on the polyamide composition. The present invention imparts excellent flame retardancy and high temperature resistance to the polyamide composition through the design and compounding of a halogen-free flame retardant system, a vinyl copolymer containing an acidic group, and a coloring system, and has a small color difference after high-temperature baking and good color stability, which can fully meet the performance requirements of high-voltage connectors, electronic appliances, and new energy industries, and is particularly suitable for high-voltage components such as high-voltage connectors, and provides a lasting warning color effect in a long-term high-temperature working environment.

[0014] In the polyamide composition provided by the present invention, the mass parts of the polyamide resin are 20-60 parts, for example, it can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or 55 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0015] The mass parts of the organic phosphinate flame retardant are 13-30 parts, for example, 14 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 27 parts or 29 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0016] The mass fraction of the synergistic flame retardant is 4-10 parts, for example, it can be 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0017] The mass fraction of the acidic group-containing vinyl copolymer is 0.2-5 parts, for example, it can be 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts or 4.8 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0018] The mass fraction of the colorant is 0.3-7 parts, for example, it can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts or 6.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0019] In the present invention, the polyamide composition has excellent flame retardancy and high temperature color stability through the design and mutual compounding of the components in specific amounts. If the mass fraction of the vinyl copolymer containing acidic groups is too low, it is difficult for it to coat the halogen-free flame retardant system, resulting in obvious color change of the polyamide composition after baking and poor heat resistance stability; if the mass fraction of the vinyl copolymer containing acidic groups is too high, the content of acidic groups in the system is too high, which will lead to strong reactivity, deterioration of high temperature resistance, and obvious baking color difference.

[0020] In the polymerization monomer of the vinyl copolymer containing acidic groups, the mass percentage of the unsaturated monomer containing acidic groups is 1%-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0021] In the polymerization monomers of the vinyl copolymer containing acidic groups of the present invention, the mass percentage of the unsaturated monomer containing acidic groups is 1%-10%, thereby providing an appropriate amount of acidic groups to effectively coat the flame retardant in the polyamide composition, thereby reducing baking color difference and improving high temperature resistant color stability; if the content of the unsaturated monomer containing acidic groups is greater than 10%, the content of acidic groups in the vinyl copolymer will be too high, the reactivity will be strong, the stability of the polyamide composition will be reduced, and the baking color difference will be large; if the content of the unsaturated monomer containing acidic groups is less than 1%, the organic phosphinate flame retardant cannot be effectively coated, resulting in discoloration of the polyamide composition during long-term thermal oxidation aging.

[0022] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0023] In the present invention, the polyamide resin includes any one of a condensation product of a dicarboxylic acid and a diamine, a condensation product of an ω-amino acid, and a ring-opening polymerization product of a cyclic lactam, or a combination of at least two thereof.

[0024] The dicarboxylic acid illustratively includes but is not limited to: any one of adipic acid, sebacic acid, dodecanedioic acid, terephthalic acid, and isophthalic acid, or a combination of at least two thereof.

[0025] The diamines illustratively include, but are not limited to, any one of hexamethylenediamine, decanediamine, dodecanediamine, butanediamine, p-phenylenediamine, and m-phenylenediamine, or a combination of at least two thereof.

[0026] The cyclic lactam illustratively includes, but is not limited to, any one of caprolactam, capryllactam, undecanolactam, and lauryl lactam, or a combination of at least two thereof.

[0027] The ω-amino acid illustratively includes, but is not limited to, any one or a combination of at least two of the ω-amino acids formed by the ring-opening of the aforementioned cyclic lactams and aminobenzoic acid.

[0028] Preferably, the polyamide resin includes any one of polyamide 66 (polyhexamethylene adipamide, PA66), polyamide 610 (PA610), polyamide 612 (PA612), polyamide 1010 (PA1010), polyamide 1012 (PA1012), polyamide 1212 (PA1212), polyamide 6 (polycaprolactam, PA6), polyamide 11 (PA11), and polyamide 12 (PA12), or a combination of at least two of them.

[0029] Preferably, the relative viscosity of a concentrated sulfuric acid solution of the polyamide resin at a concentration of 0.01 g / mL at 25° C. is 2.0-3.4, for example, it may be 2.1, 2.3, 2.5, 2.7, 2.9, 3, 3.1 or 3.3, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0030] Exemplarily, the relative viscosity test method is as follows: weigh 0.5 g of polyamide resin, transfer it to a 50 mL volumetric flask, add about 40 mL of concentrated sulfuric acid (H 2 SO 4 The mass percentage is 96%), ultrasonic vibration is applied until the polyamide resin is completely dissolved, the solution is cooled to 25°C, diluted to the scale with concentrated sulfuric acid, and mixed evenly, and the flow time of 0.01 g / mL polyamide resin solution passing through the Ubbelohde viscometer at 25°C is measured and recorded as t 1 , use the same viscometer to test the flow time of concentrated sulfuric acid, recorded as t 2 , t 1 / t 2 That is the relative viscosity of polyamide resin.

[0031] Preferably, the polyamide resin further includes 15-40 parts by mass of glass fiber, for example, the glass fiber can be 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts or 38 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0032] Preferably, the glass fiber includes any one of alkali-free glass fiber (E glass fiber), high alkali glass fiber (A glass fiber), special glass fiber (S glass fiber), D glass fiber, medium alkali glass fiber (C glass fiber), and quartz glass fiber, or a combination of at least two of them, and alkali-free glass fiber (E glass fiber) is more preferred.

[0033] Preferably, the diameter of the glass fiber is 1-30 μm, for example, it can be 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 5-15 μm is further preferred.

[0034] Preferably, the length of the glass fiber is 100-800 μm, for example, it can be 200 μm, 300 μm, 400 μm, 500 μm, 600 μm or 700 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 200-600 μm is further preferred.

[0035] As a preferred technical solution of the present invention, the glass fibers enter a melt blending device (such as a screw extruder, preferably a twin-screw extruder) in the form of continuous long fibers, and are sheared by the device to form short glass fibers with an average length of 100-800 μm, more preferably 200-600 μm, which are present in the polyamide composition.

[0036] Preferably, the organic phosphinate flame retardant has a structure as shown in Formula I:

[0037]

[0038] In Formula I, R 1 , R 2Each is independently selected from any one of C1-C6 straight or branched alkyl and C3-C6 cycloalkyl; wherein the C1-C6 straight or branched alkyl can be a straight or branched alkyl of C1, C2, C3, C4, C5, C6, illustratively including but not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-methylbutyl, n-pentyl, isopentyl, neopentyl, n-hexyl, neohexyl, etc.; the C3-C6 cycloalkyl can be a cycloalkyl of C3, C4, C5, C6, such as cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl.

[0039] In Formula I, M n+ It represents a +n-valent metal ion, where n is 2 or 3.

[0040] Preferably, the R 1 , R 2 Each is independently selected from any one of C1-C4 straight chain or branched alkyl and cyclohexyl.

[0041] Preferably, the M n+ Selected from Al 3+ or Zn 2+ .

[0042] Preferably, the organic phosphinate flame retardant includes any one of diethyl aluminum phosphinate, diethyl zinc phosphinate, dipropyl aluminum phosphinate, methyl ethyl aluminum phosphinate, methyl butyl aluminum phosphinate, and methyl cyclohexyl aluminum phosphinate, or a combination of at least two thereof.

[0043] Preferably, the organic phosphinate flame retardant comprises aluminum diethylphosphinate.

[0044] Preferably, the synergistic flame retardant includes any one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate, and zinc borate, or a combination of at least two thereof, and melamine polyphosphate and / or zinc borate are further preferred.

[0045] Preferably, the acidic group in the acidic group-containing vinyl copolymer includes any one of a carboxyl group, anhydride group, and a sulfonic acid group, or a combination of at least two of them, preferably a carboxyl group.

[0046] Preferably, the unsaturated monomer containing an acidic group comprises methacrylic acid and / or acrylic acid.

[0047] Preferably, the polymerized monomers of the acidic group-containing vinyl copolymer further include (meth)acrylate.

[0048] It should be noted that the (meth)acrylate includes acrylate and / or methacrylate.

[0049] Preferably, the (meth)acrylate includes any one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate, or a combination of at least two of them, that is, it includes any one of methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate, or a combination of at least two of them.

[0050] It should be noted that the (meth) propyl acrylate includes all feasible isomers thereof, i.e., any one or a combination of at least two of n-propyl acrylate, isopropyl acrylate, n-propyl methacrylate, and isopropyl methacrylate. The (meth) butyl acrylate also includes all feasible isomers thereof, i.e., any one or a combination of at least two of n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-butyl methacrylate, isobutyl methacrylate, and tert-butyl methacrylate.

[0051] More preferably, the (meth)acrylate includes butyl (meth)acrylate, and further preferably n-butyl (meth)acrylate.

[0052] As a preferred technical solution of the present invention, the vinyl copolymer containing acidic groups can be an ethylene-(meth)acrylic acid binary copolymer or an ethylene-(meth)acrylic acid-(meth)acrylate ternary copolymer.

[0053] Preferably, the vinyl copolymer containing an acidic group includes an ethylene-(meth)acrylic acid-(meth)acrylic acid ester copolymer, and more preferably an ethylene-methacrylic acid-butyl acrylate copolymer.

[0054] Preferably, the mass percentage of ethylene in the polymerization monomer of the vinyl copolymer containing acidic groups is 50%-80%, for example, it can be 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75% or 78%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0055] Preferably, the mass percentage of (meth)acrylate in the polymerized monomer of the acidic group-containing vinyl copolymer is 10%-49%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40% or 45%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0056] As a preferred technical solution of the present invention, the vinyl copolymer containing acidic groups is an ethylene-(meth)acrylic acid-(meth)acrylate terpolymer, and the mass percentage of ethylene in the polymerized monomer is 50%-80%, thereby making it have high flexibility and playing an excellent toughening role on the polyamide composition. The mass percentage of (meth)acrylic acid is 1%-10%, which provides an appropriate amount of carboxyl groups for the vinyl copolymer and effectively coats the flame retardant in the polyamide composition, thereby reducing the baking color difference and improving the high temperature color stability; if the content of (meth)acrylic acid is greater than 10%, the content of acidic groups in the vinyl copolymer will be too high, the reactivity will be strong, the stability of the polyamide composition will be reduced, and the baking color difference will be large. The appropriate amount of (meth)acrylate can regulate the strength and toughness of the vinyl copolymer, thereby improving the mechanical properties of the polyamide composition.

[0057] Preferably, the number average molecular weight of the acidic group-containing vinyl copolymer is 5000-50000, for example, it can be 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000 or 45000, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0058] For example, the number average molecular weight in the present invention is obtained by gel chromatography (GPC) testing, which can be obtained by using a gel chromatograph and a testing method known in the art.

[0059] The present invention does not specifically limit the source and preparation method of the vinyl copolymer containing acidic groups and the ethylene-(meth)acrylic acid-(meth)acrylate terpolymer, which can be a commercially available product or prepared by a polymerization method known in the art; the vinyl copolymer containing acidic groups and the ethylene-(meth)acrylic acid-(meth)acrylate terpolymer prepared by any polymerization method in the art are suitable for the present invention.

[0060] Illustratively, the vinyl copolymer containing acidic groups is an ethylene-methacrylic acid-butyl acrylate copolymer, which is prepared by the following method, comprising: uniformly mixing an initiator, water, tert-butyl alcohol, methacrylic acid and butyl acrylate in a reaction device, introducing ethylene into the reaction device after degassing, and conducting a polymerization reaction to obtain the ethylene-methacrylic acid-butyl acrylate copolymer.

[0061] Preferably, the initiator comprises an azo initiator, and more preferably azobisisobutyronitrile.

[0062] Preferably, the reaction apparatus comprises an autoclave.

[0063] Preferably, the polymerization reaction temperature is 60-100°C, for example, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0064] Preferably, the polymerization reaction time is 2-10 h, for example, it can be 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h or 9.5 h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0065] Preferably, the polymerization reaction pressure is 20-30 MPa, for example, it can be 21 MPa, 22 MPa, 23 MPa, 24 MPa, 25 MPa, 26 MPa, 27 MPa, 28 MPa or 29 MPa, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range; the pressure can be maintained by continuously introducing ethylene.

[0066] Preferably, the polymerization reaction obtains an emulsion with a solid content of 15-25%, and the solid content of the emulsion may be 16%, 18%, 20%, 22% or 24%, etc. The emulsion is purified and dried to obtain a random copolymerized ethylene-methacrylic acid-butyl acrylate copolymer.

[0067] Preferably, the colorant comprises a combination of a white pigment, a cerium sulfide pigment and an orange organic dye.

[0068] As a preferred technical solution of the present invention, white pigment, cerium sulfide pigment and orange organic dye are used in combination to synergistically construct a composite coloring system, which not only has excellent coloring ability and can be matched into the color RAL2010, which is an ideal police color, but also has excellent color stability.

[0069] Preferably, the colorant comprises the following components in parts by mass:

[0070] White pigment 0.1-5 parts

[0071] Cerium sulfide pigment 0.1-1 part

[0072] Orange organic dye 0.1-1 part;

[0073] Specifically, the mass fraction of the white pigment is 0.1-5 parts, for example, it can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0074] The mass fraction of the cerium sulfide pigment is 0.1-1 part, for example, it can be 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0075] The mass proportion of the orange organic dye is 0.1-1 part, for example, it can be 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0076] Preferably, the white pigment includes any one of zinc sulfide, lithopone, and titanium dioxide, or a combination of at least two of them.

[0077] Preferably, the cerium sulfide pigment includes any one of Pigment Orange 75, Pigment Orange 78, and Pigment Red 265, or a combination of at least two of them.

[0078] Preferably, the orange organic dye comprises solvent orange 116 .

[0079] As a preferred technical solution of the present invention, the solvent orange 116, white pigment and cerium sulfide pigment are reasonably matched to synergistically construct a composite coloring system with excellent coloring ability, which can be matched into the ideal warning color RAL 2010. Moreover, the present invention has found that in the polyamide composition, the color value b value of the white pigment increases after high-temperature baking, while the color value b value of the solvent orange 116 decreases after high-temperature baking. The solvent orange 116, white pigment and cerium sulfide pigment work together to reduce the high-temperature baking color difference of the polyamide composition and improve the high-temperature resistant color stability.

[0080] It should be noted that the polyamide composition provided by the present invention may also include any other additives that are added with motivation in the art.

[0081] Preferably, the polyamide composition further comprises an antioxidant and / or a lubricant.

[0082] Preferably, the polyamide composition further includes 0.01-1 parts of antioxidant by weight, and the antioxidant may be in an amount of 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts or 0.7 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0083] Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a phosphite antioxidant, a cuprous halide composite antioxidant, and a benzophenone antioxidant, or a combination of at least two thereof.

[0084] Preferably, the polyamide composition further includes 0.01-1 parts of lubricant by mass, and the mass parts of the lubricant can be 0.02 parts, 0.05 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts or 0.9 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0085] Preferably, the lubricant includes any one of hydrocarbon lubricants, ester lubricants, alcohol lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants, or a combination of at least two thereof, and ester lubricants are more preferred.

[0086] Preferably, the ester lubricant includes any one of fatty acid ester, polyol ester, polyethylene glycol ester, or a combination of at least two thereof.

[0087] Preferably, the polyamide composition comprises the following components in parts by mass:

[0088]

[0089]

[0090] Preferably, the color code of the polyamide composition is RAL2010.

[0091] In the polyamide composition provided by the present invention, polyamide resin is used as the main resin. Preferably, the mass percentage of the polyamide resin in the polyamide composition is 35-60%, for example, it can be 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55% or 58%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0092] The glass fiber has a reinforcing effect. Preferably, the mass percentage of the glass fiber in the polyamide composition is 15-40%, for example, it can be 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35% or 38%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0093] Preferably, the mass percentage of the vinyl copolymer containing acidic groups in the polyamide composition (ethylene-(meth)acrylic acid-(meth)acrylate copolymer) is 0.2-5%, for example, it can be 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 3%, 3.5%, 4% or 4.5%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0094] In a second aspect, the present invention provides a method for preparing the polyamide composition as described in the first aspect, the preparation method comprising:

[0095] Mixing a polyamide resin, an organic phosphinate flame retardant, a synergistic flame retardant, a vinyl copolymer containing an acidic group, and a colorant to obtain a premix;

[0096] The premix is ​​melt-blended and then extruded to obtain the polyamide composition.

[0097] Preferably, the mixed material further comprises an antioxidant and / or a lubricant.

[0098] Preferably, the mixing is carried out in a high mixer.

[0099] Preferably, the mixing time is 1-20 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 12 min, 15 min or 18 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 3-10 min is further preferred.

[0100] Preferably, the mixing temperature is 15-40°C, for example, it can be 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C or 38°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and room temperature is further preferred.

[0101] Preferably, the melt-blended material further comprises glass fibers.

[0102] Preferably, the melt blending is carried out in a screw extruder, and the screw extruder is preferably a twin-screw extruder.

[0103] Preferably, the temperature of each section of the screw barrel of the screw extruder is independently 150-280°C, for example, it can be 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 160-250°C is further preferred.

[0104] Preferably, the head temperature of the screw extruder is 220-280°C, for example, it can be 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C or 270°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 230-260°C is further preferred.

[0105] Preferably, the screw speed of the screw extruder is 200-1000rpm, for example, it can be 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm or 900rpm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 300-800pm is further preferred.

[0106] Preferably, the screw extruder has a screw length-to-diameter ratio of (32-52):1, for example, 36:1, 40:1, 44:1 or 48:1, etc., and more preferably (36-48):1.

[0107] Preferably, the extrusion further includes the steps of drawing, cooling and pelletizing.

[0108] In a preferred technical solution, the method for preparing the polyamide composition comprises:

[0109] A polyamide resin, an organic phosphite flame retardant, a synergistic flame retardant, a vinyl copolymer containing an acidic group, a white pigment, a cerium sulfide pigment, an orange organic dye, an optional antioxidant and an optional lubricant are mixed for 3-10 minutes to obtain a premix; the premix is ​​added to the main feeding hopper of a twin-screw extruder, and glass fiber is added from the side feeding hopper of the sixth screw barrel, and the premix is ​​fully plasticized, melt-blended and then extruded, and the polyamide composition is obtained after drawing, cooling and pelletizing; wherein the screw speed of the twin-screw extruder is 300-800rpm, the screw aspect ratio is (36-48):1, the temperature of each screw barrel section is independently 160°C-250°C, and the head temperature is 230°C-260°C.

[0110] In a third aspect, the present invention provides a use of the polyamide composition as described in the first aspect in electronic appliances, high-voltage connectors, energy storage devices or automotive parts.

[0111] Preferably, the polyamide composition is applied to a housing of a high voltage connector.

[0112] Compared with the prior art, the present invention has the following beneficial effects:

[0113] (1) In the polyamide composition provided by the present invention, an organic phosphite flame retardant and a synergistic flame retardant are compounded to construct a halogen-free flame retardant system. By designing and compounding the halogen-free flame retardant system, the vinyl copolymer containing an acidic group, and the coloring system, the polyamide composition has excellent flame retardancy and high temperature resistance, small color difference after high-temperature baking, and good color stability, which can fully meet the performance requirements of high-voltage connectors, electronic appliances, and new energy industries.

[0114] (2) Based on the design, reasonable matching and optimization of each component, the polyamide composition of the present invention achieves a flame retardant effect of 0.8mmV-0 level, presents a RAL2010 signal orange color, has a color difference ΔE<11 after baking at 140°C for 168h, and has a tensile strength of ≥106MPa. It has excellent flame retardancy, high temperature color stability and mechanical properties, is suitable for high-voltage components such as high-voltage connectors, and provides a lasting warning color effect in a long-term high-temperature working environment. DETAILED DESCRIPTION

[0115] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0116] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0117] Preparation Example 1

[0118] A vinyl copolymer containing an acidic group, specifically an ethylene-methacrylic acid-butyl acrylate copolymer, is prepared by the following method:

[0119] Ethylene, methacrylic acid and n-butyl acrylate are used as polymerization monomers for emulsion polymerization, wherein the mass percentages of ethylene, methacrylic acid and n-butyl acrylate in the polymerization monomers are 60%, 5% and 35% respectively; the specific preparation process is as follows: azobisisobutyronitrile (AIBN), pure water, tert-butyl alcohol (the mass ratio of pure water to tert-butyl alcohol is 5.3:1), methacrylic acid and n-butyl acrylate are placed in an autoclave and stirred evenly to obtain a mixture; the concentration of AIBN in the mixture is 0.01 mol / L, and the solvent ( The mass percentage of pure water and tert-butyl alcohol is 98.4%; after degassing the reactor, ethylene is charged into it, and a polymerization reaction is carried out at a temperature of 80° C. and a pressure of 25 MPa. During the reaction process, ethylene is continuously added and the pressure is kept constant. The polymerization reaction time is about 6 hours, and an emulsion with a solid content of 20% is obtained; the emulsion is purified and dried to obtain the ethylene-methacrylic acid-butyl acrylate copolymer, hereinafter referred to as vinyl copolymer A, and its number average molecular weight is 18000 as measured by gel chromatography (GPC).

[0120] Preparation Example 2

[0121] A vinyl copolymer containing an acidic group, which is an ethylene-methacrylic acid-butyl acrylate copolymer, which is different from Preparation Example 1 only in that the mass percentages of ethylene, methacrylic acid and n-butyl acrylate in the polymerization monomers are 80%, 1% and 19% respectively, and the types, amounts and preparation process parameters of other materials are the same as those in Preparation Example 1, to obtain an ethylene-methacrylic acid-butyl acrylate copolymer, hereinafter referred to as vinyl copolymer B, and its number average molecular weight measured by GPC is 11000.

[0122] Preparation Example 3

[0123] A vinyl copolymer containing an acidic group, which is an ethylene-methacrylic acid-butyl acrylate copolymer, which is different from Preparation Example 1 only in that the mass percentages of ethylene, methacrylic acid and n-butyl acrylate in the polymerization monomers are 50%, 10% and 40% respectively, and the types, amounts and preparation process parameters of other materials are the same as those in Preparation Example 1, to obtain an ethylene-methacrylic acid-butyl acrylate copolymer, hereinafter referred to as vinyl copolymer C, and its number average molecular weight measured by GPC is 20000.

[0124] Preparation Example 4

[0125] A vinyl copolymer containing an acidic group, which is an ethylene-methacrylic acid-butyl acrylate copolymer, which is different from Preparation Example 1 only in that the mass percentages of ethylene, methacrylic acid and n-butyl acrylate in the polymerization monomers are 60%, 0.5% and 39.5% respectively, and the types, amounts and preparation process parameters of other materials are the same as those in Preparation Example 1, to obtain an ethylene-methacrylic acid-butyl acrylate copolymer, hereinafter referred to as vinyl copolymer D, and its number average molecular weight measured by GPC is 17000.

[0126] Preparation Example 5

[0127] A vinyl copolymer containing an acidic group, which is an ethylene-methacrylic acid-butyl acrylate copolymer, which is different from Preparation Example 1 only in that the mass percentages of ethylene, methacrylic acid and n-butyl acrylate in the polymerization monomers are 60%, 15% and 25% respectively, and the types, amounts and preparation process parameters of other materials are the same as those in Preparation Example 1, to obtain an ethylene-methacrylic acid-butyl acrylate copolymer, hereinafter referred to as vinyl copolymer E, and its number average molecular weight measured by GPC is 21000.

[0128] In the following specific implementation of the present invention, the specific information of the materials used is as follows:

[0129] (1) Polyamide resin

[0130] PA66, specifically PA66 EPR24, with a relative viscosity of 2.4, purchased from Shenma Group;

[0131] PA6, specifically PA6 HY2800A, with a relative viscosity of 2.8, was purchased from Haiyang Chemical Fiber.

[0132] (2) Glass fiber

[0133] ECS10-03-568H, purchased from Jushi.

[0134] (3) Organic phosphinate flame retardant

[0135] Aluminum diethylphosphinate, Exolit OP 1230, was purchased from Clariant.

[0136] (4) Synergistic flame retardants

[0137] Melamine polyphosphate, Budit 3141, was purchased from Budit.

[0138] (5) Vinyl copolymers containing acidic groups

[0139] Vinyl copolymer A, the polymerized monomers are as follows by mass percentage: 60% ethylene, 5% methacrylic acid, 35% n-butyl acrylate; from Preparation Example 1;

[0140] Vinyl copolymer B, the polymerized monomers are as follows by mass percentage: ethylene 80%, methacrylic acid 1%, n-butyl acrylate 19%; from Preparation Example 2;

[0141] Vinyl copolymer C, the polymerized monomers are as follows by mass percentage: ethylene 50%, methacrylic acid 10%, n-butyl acrylate 40%; from Preparation Example 3;

[0142] Vinyl copolymer D, the polymerized monomers are as follows by mass percentage: 60% ethylene, 0.5% methacrylic acid, 39.5% n-butyl acrylate; from Preparation Example 4;

[0143] Vinyl copolymer E, the polymerized monomers are as follows by mass percentage: 60% ethylene, 15% methacrylic acid, and 25% n-butyl acrylate; from Preparation Example 5.

[0144] (6) Ethylene-butyl acrylate-glycidyl methacrylate copolymer: Elvaloy PTW, purchased from Dupont Company.

[0145] (7) White pigment

[0146] Zinc sulfide HD-S, purchased from Sachliben;

[0147] Titanium dioxide R103 was purchased from Dupont.

[0148] (8) Cerium sulfide pigment

[0149] Pigment Orange 75, purchased from Baotou Hongbote;

[0150] Pigment Orange 78 was purchased from Baotou Hongbote.

[0151] (9) Orange organic dye

[0152] Solvent Orange 116 and Oracet Orange 220 were purchased from BASF.

[0153] (10) Antioxidants

[0154] Hindered phenol antioxidant, IRGANOX 1098, was purchased from BASF.

[0155] (11) Lubricant

[0156] Ester lubricant, TR044W, was purchased from Struktol.

[0157] Example 1

[0158] A polyamide composition and a preparation method thereof, wherein the polyamide composition comprises the following components in parts by mass:

[0159]

[0160]

[0161] The preparation method of the polyamide composition is as follows:

[0162] (1) PA66 EPR24, aluminum diethylphosphinate, polyphosphate melamine, vinyl copolymer A, zinc sulfide HD-S, pigment orange 75, solvent orange 116, antioxidant IRGANOX 1098 and lubricant TR044W were mixed in a high-speed mixer for 5 minutes according to the above formula to obtain a premix;

[0163] (2) adding the premix into the main feeding hopper of a twin-screw extruder, and adding the glass fiber from the side feeding hopper of the sixth screw barrel; the screw speed of the twin-screw extruder is 400 rpm, the screw aspect ratio is 40:1, the temperatures of the screw barrels of each section are 160° C., 250° C., 240° C., 240° C., 220° C., 220° C., 220° C., 230° C., and 230° C., respectively, and the die temperature is 250° C., so that the components are fully plasticized, melt-blended, and then extruded, and the polyamide composition is obtained through drawing, cooling, and pelletizing.

[0164] Examples 2-10, Comparative Examples 1-6

[0165] A polyamide composition, which differs from Example 1 only in the types and / or amounts of components, as shown in Tables 1 and 2, wherein "--" represents that the component is not added; the preparation method of the polyamide composition is the same as that of Example 1.

[0166] Table 1

[0167]

[0168]

[0169] Table 2

[0170]

[0171]

[0172] The performance test of the polyamide compositions provided in Examples 1-10 and Comparative Examples 1-6 was carried out in the following manner:

[0173] (1) Flame retardancy: vertical combustion test, injection molding 125mm×13mm×0.8mm burning specimen, test its flame retardancy according to UL 94 standard;

[0174] (2) Color difference: Injection mold a 60mm×60mm×2mm color plate, and test the L, a, and b values ​​according to CIE 2000. L represents lightness, a represents red and green, and b represents yellow and blue. At this time, they are recorded as L1, a1, and b1. For RAL2010 signal orange, its color standard values ​​are L1: 53-57, a1: 39-41, and b1: 41-43. Then place the color plate in a 140℃ oven and bake it for 168h. Then take it out and test the L, a, and b values. At this time, they are recorded as L2, a2, and b2. The color difference ΔE can be calculated by the following formula:

[0175]

[0176] (3) Tensile strength: Injection molded ISO tensile specimens were tested for tensile strength according to ISO 527-2:2012; the test data are shown in Table 3:

[0177] Table 3

[0178]

[0179]

[0180] According to the performance test data in Table 3, the polyamide composition has excellent flame retardancy through the design and compounding of the halogen-free flame retardant system, the vinyl copolymer containing acidic groups, and the composite coloring system, and achieves 0.8mm V-0 flame retardancy, has significantly improved high temperature baking color stability, and the color difference ΔE after baking at 140°C for 168h is less than 11, which can be as low as 8.0-10.7. At the same time, the mechanical strength is high, and the tensile strength is 106-163MPa.

[0181] In the present invention, the vinyl copolymer containing an acidic group can coat the flame retardant. Taking the ethylene-methacrylic acid-butyl acrylate copolymer in the specific embodiment as an example, by designing the content of methacrylic acid in the polymerized monomer to be 1%-10%, the flame retardant can be fully and effectively coated, thereby improving the heat resistance stability of the polyamide composition and reducing the baking color difference. The content of methacrylic acid in the ethylene-methacrylic acid-butyl acrylate copolymer of Comparative Example 1 is too low, and it is difficult to achieve effective coating, resulting in a large color difference after baking and insufficient high temperature resistance stability; the content of methacrylic acid in the ethylene-methacrylic acid-butyl acrylate copolymer of Comparative Example 2 is too high, resulting in its strong reactivity, so the color difference after baking is also large.

[0182] The present invention introduces a specific vinyl copolymer containing an acidic group to coat the flame retardant, so that the polyamide composition has both excellent flame retardancy and high temperature color stability. In Comparative Example 3, ethylene-methacrylic acid-butyl acrylate copolymer was not used, and the color difference after baking was large. In Comparative Example 4, the amount of ethylene-methacrylic acid-butyl acrylate copolymer added was too small, and it did not play a significant role in color stability. In Comparative Example 5, the amount of ethylene-methacrylic acid-butyl acrylate copolymer added was too high, which not only reduced the flame retardancy to V-1 level, but also had a large color difference after baking and poor high temperature stability. Comparative Example 6 used other types of vinyl copolymers, which did not contain acidic groups and did not have the effect of improving the color difference after thermal baking.

[0183] In the present invention, it is preferred to use white pigment, cerium sulfide pigment and orange organic dye to construct a composite coloring system, which is compounded with other components to provide an ideal warning color while also having better high temperature resistant color stability. In the coloring systems of Examples 9 and 10, color orange 75 and solvent orange 116 are not used at the same time, and their colors deviate far from RAL2010 and cannot meet the requirements, and the color difference after baking is also relatively large.

[0184] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the polyamide composition and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A polyamide composition, characterized in that The polyamide composition comprises the following components in parts by mass: Polyamide resin 20-60 parts 13-30 parts of organic phosphinate flame retardant Synergistic flame retardant 4-10 parts 0.2-5 parts of vinyl copolymer containing acidic groups Colorant 0.3-7 parts; The polymerizable monomers of the vinyl copolymer containing acidic groups include a combination of ethylene, (meth)acrylate and unsaturated monomers containing acidic groups, and the mass percentage of the unsaturated monomers containing acidic groups in the polymerizable monomers is 1%-10%; The acidic group-containing unsaturated monomer includes methacrylic acid and / or acrylic acid; The colorant comprises the following components by mass: White pigment 0.1-5 parts Cerium sulfide pigment 0.1-1 part Orange organic dye 0.1-1 part; The cerium sulfide pigment includes any one of Pigment Orange 75, Pigment Orange 78, and Pigment Red 265, or a combination of at least two thereof; The orange organic dye includes solvent orange 116 .

2. The polyamide composition according to claim 1, characterized in that The polyamide resin includes any one of polyamide 66, polyamide 610, polyamide 612, polyamide 1010, polyamide 1012, polyamide 1212, polyamide 6, polyamide 11, and polyamide 12, or a combination of at least two of them.

3. The polyamide composition according to claim 1, characterized in that The polyamide resin further comprises 15-40 parts by mass of glass fiber.

4. The polyamide composition according to claim 3, characterized in that The glass fiber includes any one of alkali-free glass fiber, high-alkali glass fiber, special glass fiber, D glass fiber, medium-alkali glass fiber, and quartz glass fiber, or a combination of at least two thereof.

5. The polyamide composition according to claim 4, characterized in that The glass fiber includes alkali-free glass fiber.

6. The polyamide composition according to claim 1, characterized in that The organic phosphinate flame retardant has a structure as shown in Formula I: Formula I; Wherein, R1 and R2 are each independently selected from any one of C1-C6 straight chain or branched chain alkyl and C3-C6 cycloalkyl; M n+ It represents a +n-valent metal ion, where n is 2 or 3.

7. The polyamide composition according to claim 6, characterized in that The R1 and R2 are each independently selected from any one of a C1-C4 straight chain or branched chain alkyl group and a cyclohexyl group.

8. The polyamide composition according to claim 6, characterized in that The M n+ Selected from Al 3+ or Zn 2+ .

9. The polyamide composition according to claim 6, characterized in that The organic phosphinate flame retardant includes aluminum diethylphosphinate.

10. The polyamide composition according to claim 1, characterized in that The synergistic flame retardant includes any one of melamine polyphosphate, melamine aluminum polyphosphate, melamine magnesium polyphosphate, melamine zinc polyphosphate, and zinc borate, or a combination of at least two thereof.

11. The polyamide composition according to claim 10, characterized in that The synergistic flame retardant includes melamine polyphosphate and / or zinc borate.

12. The polyamide composition according to claim 1, characterized in that The (meth)acrylate includes any one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate, or a combination of at least two thereof.

13. The polyamide composition according to claim 12, characterized in that The (meth)acrylate includes butyl (meth)acrylate.

14. The polyamide composition according to claim 1, characterized in that The acidic group-containing vinyl copolymer includes ethylene-methacrylic acid-butyl acrylate copolymer.

15. The polyamide composition according to claim 1, characterized in that The mass percentage of ethylene in the polymerized monomers of the vinyl copolymer containing acidic groups is 50%-80%.

16. The polyamide composition according to claim 1, characterized in that The mass percentage of (meth)acrylate in the polymerized monomer of the vinyl copolymer containing acidic groups is 10%-49%.

17. The polyamide composition according to claim 1, characterized in that The number average molecular weight of the vinyl copolymer containing an acidic group is 5,000-50,000.

18. The polyamide composition according to claim 1, characterized in that The white pigment includes any one of zinc sulfide, lithopone, and titanium dioxide, or a combination of at least two of them.

19. The polyamide composition according to claim 1, characterized in that The polyamide composition further comprises an antioxidant and / or a lubricant.

20. The polyamide composition according to claim 19, characterized in that The polyamide composition further comprises 0.01-1 parts by weight of an antioxidant.

21. The polyamide composition according to claim 19, characterized in that The antioxidant includes any one of a hindered phenol antioxidant, a phosphite antioxidant, a cuprous halide composite antioxidant, and a benzophenone antioxidant, or a combination of at least two of them.

22. The polyamide composition according to claim 19, characterized in that The polyamide composition further comprises 0.01-1 parts by mass of a lubricant.

23. The polyamide composition according to claim 19, characterized in that The lubricant includes any one of hydrocarbon lubricants, ester lubricants, alcohol lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants, or a combination of at least two of them.

24. The polyamide composition according to claim 1, characterized in that The polyamide composition comprises the following components in parts by mass: Polyamide resin 20-60 parts Glass fiber 15-40 parts 13-30 parts of organic phosphinate flame retardant Synergistic flame retardant 4-10 parts Ethylene-(meth)acrylic acid-(meth)acrylate copolymer 0.2-5 parts White pigment 0.1-5 parts Cerium sulfide pigment 0.1-1 part Solvent Orange 1160.1-1 part Antioxidant 0-1 part Lubricant 0-1 part.

25. The polyamide composition according to claim 1, characterized in that The color code of the polyamide composition is RAL2010.

26. A method for preparing a polyamide composition according to claim 1, characterized in that: The preparation method comprises: Mixing a polyamide resin, an organic phosphinate flame retardant, a synergistic flame retardant, a vinyl copolymer containing an acidic group, and a colorant to obtain a premix; The premix is ​​melt-blended and then extruded to obtain the polyamide composition.

27. The preparation method according to claim 26, characterized in that: The mixed material also includes an antioxidant and / or a lubricant.

28. The preparation method according to claim 26, characterized in that: The mixing time is 1-20 min.

29. The preparation method according to claim 28, characterized in that: The mixing time is 3-10 min.

30. The preparation method according to claim 26, characterized in that: The melt-blended material also includes glass fibers.

31. The preparation method according to claim 26, characterized in that: The melt blending is carried out in a screw extruder.

32. The preparation method according to claim 31, characterized in that: The temperature of each section of the screw barrel of the screw extruder is independently 150-280°C.

33. The preparation method according to claim 32, characterized in that: The temperature of each section of the screw barrel of the screw extruder is independently 160-250°C.

34. The preparation method according to claim 31, characterized in that: The head temperature of the screw extruder is 220-280°C.

35. The preparation method according to claim 34, characterized in that: The head temperature of the screw extruder is 230-260°C.

36. The preparation method according to claim 26, characterized in that: The method further comprises the steps of drawing, cooling and pelletizing after the extrusion.

37. Use of the polyamide composition according to any one of claims 1 to 25 in electronic appliances, high-voltage connectors, energy storage devices or automotive parts.

38. The use according to claim 37, characterized in that The polyamide composition is applied to a housing of a high-voltage connector.

Citation Information

Patent Citations

  • Flame-retardant polyamide composition and product prepared therefrom

    CN102952391A

  • Fire-retardant polyamides comprising pvp

    CN110446756A

  • Flame resistant polymer composition with improved color stability

    EP1950238A2

  • Halogen free flame retardant polyamide composition

    CN104619765A